'Think big' or 'small is beautiful'? An empirical analysis of characteristics and determinants of success of sustainable crowdfunding projects. (2018) - Hörisch, Jacob
This paper deals with crowdfunding for sustainable ventures. It uses an empirical dataset gained from the two largest sustainability-oriented crowdfunding platforms in Germany. In a first step, common characteristics of sustainable crowdfunding projects are identified and categorised based on an established framework for classifying sustainable entrepreneurship. In a second step, linear and logistic regression models are used to analyse the drivers of financial and marketing success of sustainable crowdfunding projects. The analysis reveals that only few ecopreneurial, growth-oriented ventures can be found among sustainable crowdfunding projects and shows that those projects which do not aim at high levels of market impact and growth are more likely to reach their funding targets. Based on the results, recommendations for sustainable entrepreneurs who intend to make use of crowdfunding are formulated and the potential contribution of crowdfunding to sustainability transitions is discussed.